Penerapan Metode Bernyanyi Dalam Peningkatan Prestasi Pembelajaran Bahasa Arab Di Kelas Tinggi MI Ar-Rahman Jetis Mojokerto - Widiyanti, Diya Sri; Jannah, Annisya’i Afifatul (LPPM Institut Al Azhar Menganti Gresik, 2023)
This research aims to determine the effect of the singing method in improving Arabic language learning achievement at MI AR-Rahman, Parengan Village, Jetis District, Mojokerto Regency. This research use desciptive qualitative approach. The subjects in this research consisted of two classes, namely class IV and class V. The data collection techniques used interviews, observation, questionnaires, test questions, documentation. Meanwhile, the data analysis technique used is qualitative descriptive analysis. It can be concluded that the singing method can be said to be successful and suitable for use to improve the ability to remember Arabic vocabulary for MI AR-Rahman Dusun Parengan students, Parengan Village, Jetis District, Mojokerto Regency, East Java.